Analysis of Serum Chemerin Levels in Type 2 Diabetes Mellitus Patients - Fauziah Fauziah; Suci Aprianti; Liong Boy Kurniawan (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Chemerin is an adipokine involved in inflammation, adipogenesis, angiogenesis, and energy metabolism. Diabetes Mellitus (DM) is a group of metabolic diseases with hyperglycemia characteristics that occur due to abnormalities in insulin secretion, insulin action, or both. This study aimed to determine serum chemerin levels in patients with Type 2 Diabetes Mellitus (T2DM) between controlled and uncontrolled groups. This study was an analytical observational study with a cross-sectional approach. The study samples were all patients diagnosed with T2DM who had HbA1c test results and met the inclusion and exclusion criteria. Serum chemerin was measured using the ELISA method. The Kolmogorov-Smirnov, Chi-Square, Pearson, and independent T-test statistically analyzed the data. The subjects were 60 controlled and uncontrolled DM patients, 29 males and 31 females. There was a difference in serum chemerin levels in the controlled and uncontrolled DM group (5.73±2.3 ng/mL with 6.87±1.7 ng/mL, p=0.40). There was a positive correlation between chemerin levels and HbA1c (r=0.266; p=0.040). Serum chemerin levels of patients with uncontrolled DM were higher than in patients with controlled DM. Serum chemerin will increase along with the increase of HbA1c level.